TVMM: an R package for testing hypothesis on mean vectors - Alves, Henrique José de Paula; Furtado Ferreira, Daniel; Deivide de Oliveira Batista, Ben (Brazilian Journal of Biometrics, 2023)
TThe Multivariate Tests for the Vector of Means (TVMM) package has six functions: T2O function, which computes Hotelling original’s T² test; T2Boot function, which computes the parametric bootstrap version of the original T2 test; T2RobustBoot function, which computes the robust parametric bootstrap version of the T2Boot test; LRTTrace function, which computes the asymptotic version of the likelihood ratio test (LRT) using the trace operator; LRTTBoot function, which computes the parametric bootstrap version of the LRTTrace and the LRTTRBoot, which computes the robust version of the LRTTBoot. The alternative test versions of the LRT have the advantage of being valid for high-dimensional data. We describe the methods and illustrate the use of the TVMM package with real data on soil properties.